PSYCHOLOGICAL AND PEDAGOGICAL COMPETENCE OF FUTURE PRESCHOOL TEACHERS IN THE SYSTEM OF INCLUSIVE EDUCATION - Тусупова, Айжан (Pedagogy and Psychology, 2023)
An analysis of the main development trends of children with special educational needs allows us to highlight a number of reasons that set strategic directions in determining ways to achieve a new quality of inclusive education, creating promising paradigms, concepts for building a system of preschool education and training, taking into account the integration of children with problems in society. Inclusive education is understood as a complex activity of pedagogical collectives, parents, and leaders of the entire educational system to create, master, use the philosophy of inclusive education. The inclusive education system includes educational institutions of preschool, secondary, vocational and higher education. Its goal is to create a barrier-free environment in the education and training of people with disabilities. The article gives an idea of ​​inclusion as the realization of the right to education of children with special educational needs, considers aspects of inclusive education.